Odpowiedzi

Najlepsza Odpowiedź!
2009-11-20T14:34:52+01:00
Rozwiąż nierówność

log⅓(x) > log x (3) - 2.5 zał. x>0
należy zamienic podstawę log.

log⅓(x) > log ⅓ (3)/log ⅓ x - 2.5
log⅓(x) > log ⅓ (1/3)⁻¹/log ⅓ x - 2.5
log⅓(x) > -1/log ⅓ x - 2.5
log⅓(x) +1/log ⅓ x + 2.5 >0
podstawiam zmienną
log⅓(x) =t
t+1/t+2,5>0 /*t i x>1 →t<0
t²+2,5t+1<0
Δ=6,25-4=2,25
√Δ=1,5
t=-2 ,t=-1/2
t>-2 i t<-1/2
log⅓(x)>-2 i log⅓(x)<-1/2
x<(1/3)⁻² i x>(1/3)^(-1/2) i x>1
x<9 i x>√3 i x>1
czyli x∈(√3,9)
t+1/t+2,5>0 /*t i 0<x<1 →t>0
t²+2,5t+1>0
Δ=6,25-4=2,25
√Δ=1,5
t=-2 ,t=-1/2 i t>0
t>-1/2
log⅓(x)>-1/2
x<(1/3)^(-1/2) i 0 <x<1
x<√3 i 0<x<1
czyli x∈(0,1)

ostatecznie: x∈(0,1)u(√3,9)
6 3 6